Conflicting Subcultures in Mergers and Acquisitions: a Longitudinal Study of Integrating a Radical Internet Firm into a Bureaucratic Telecoms Firm. (27th January 2016) - van Marrewijk, Alfons
Abstract : Media and telecommunications companies face the problem of how to integrate diametrically opposite radical internet firms after acquisition. Extant mergers and acquisitions (M&A) studies report that differences in the organizational culture are important in the cultural integration process. Frequently, M&A research assumes organizational cultures to be homogeneous and unified, but a large body of organizational literature suggests that organizations should be understood as heterogeneous living worlds in which employees construct their own subcultures. The paper focuses on the question of how such subcultures affect the long‐term cultural integration of merged firms. A 12‐year longitudinal field study in the Netherlands examined the integration of iPioneer into Telcom. The findings of the study show how three subcultures in iPioneer influenced the cultural integration process. The paper makes a contribution to the academic debate on cultural integration in domestic M&A by acknowledging that the numerous coexisting subcultures influence cultural integration in the complex process of post‐acquisition integration.